GLP-1 modulates the supramammillary nucleus-lateral hypothalamic neurocircuit to control ingestive and motivated behavior in a sex divergent manner - Lorena López-Ferreras; Kim Eerola; Devesh Mishra; Olesya T. Shevchouk; Jennifer E. Richard; Fredrik H. Nilsson; Matthew R. Hayes; Karolina P. Skibicka (Elsevier, 2019)
Objective: The supramammillary nucleus (SuM) is nestled between the lateral hypothalamus (LH) and the ventral tegmental area (VTA). This neuroanatomical position is consistent with a potential role of this nucleus to regulate ingestive and motivated behavior. Here neuroanatomical, molecular, and behavior approaches are utilized to determine whether SuM contributes to ingestive and food-motivated behavior control. Methods: Through the application of anterograde and retrograde neural tract tracing with novel designer viral vectors, the current findings show that SuM neurons densely innervate the LH in a sex dimorphic fashion. Glucagon-like peptide-1 (GLP-1) is a clinically targeted neuro-intestinal hormone with a well-established role in regulating energy balance and reward behaviors. Here we determine that GLP-1 receptors (GLP-1R) are expressed throughout the SuM of both sexes, and also directly on SuM LH-projecting neurons and investigate the role of SuM GLP-1R in the regulation of ingestive and motivated behavior in male and female rats. Results: SuM microinjections of the GLP-1 analogue, exendin-4, reduced ad libitum intake of chow, fat, or sugar solution in both male and female rats, while food-motivated behaviors, measured using the sucrose motivated operant conditioning test, was only reduced in male rats. These data contrasted with the results obtained from a neighboring structure well known for its role in motivation and reward, the VTA, where females displayed a more potent response to GLP-1R activation by exendin-4. In order to determine the physiological role of SuM GLP-1R signaling regulation of energy balance, we utilized an adeno-associated viral vector to site-specifically deliver shRNA for the GLP-1R to the SuM. Surprisingly, and in contrast to previous results for the two SuM neighboring sites, LH and VTA, SuM GLP-1R knockdown increased food seeking and adiposity in obese male rats without altering food intake, body weight or food motivation in lean or obese, female or male rats. Conclusion: Taken together, these results indicate that SuM potently contributes to ingestive and motivated behavior control; an effect contingent on sex, diet/homeostatic energy balance state and behavior of interest. These data also extend the map of brain sites directly responsive to GLP-1 agonists, and highlight key differences in the role that GLP-1R play in interconnected and neighboring nuclei. Keywords: GLP-1, Supramammillary, Lateral hypothalamic area, Body weight, Operant conditioning